2021
DOI: 10.5603/rpor.a2021.0014
|View full text |Cite
|
Sign up to set email alerts
|

Dose accuracy improvement on head and neck VMAT treatments by using the Acuros algorithm and accurate FFF beam calibration

Abstract: Background The purpose of this study was to assess dose accuracy improvement and dosimetric impact of switching from the anisotropic analytical algorithm (AA) to the Acuros XB algorithm (AXB) when performing an accurate beam calibration in head and neck (H&N) FFF-VMAT treatments. Materials and methods Twenty H&N cancer patients treated with FFF-VMAT techniques were included. Calculations were performed with the AA and AXB algorithm (dose-to-water — AXB w … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…However, this finding also demonstrates the need to set variable limits when monitoring a system like the RPA; different RT facilities use different TPS/algorithm combinations. Specifically, Martin‐Martin et al 34 . found that AAA and Acuros can differ by up to 6.3% if not properly characterized for VMAT head and neck flattening filter‐free RT cases—well beyond a clinical threshold, though this does not necessarily reflect the quality of the plan.…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding also demonstrates the need to set variable limits when monitoring a system like the RPA; different RT facilities use different TPS/algorithm combinations. Specifically, Martin‐Martin et al 34 . found that AAA and Acuros can differ by up to 6.3% if not properly characterized for VMAT head and neck flattening filter‐free RT cases—well beyond a clinical threshold, though this does not necessarily reflect the quality of the plan.…”
Section: Discussionmentioning
confidence: 99%